Remote extradural hematoma after supratentorial brain tumor surgery: A rare complication of a routine surgery - Punia, Prashant; Chugh, Ashish; Gotecha, Sarang (Nepal Journal of Neuroscience, 2021)
Background: Hemorrhages in the surgical cavity post resection of tumor aren’t uncommon and neurosurgeons are well versed with this entity, however occurrence of an Extra Dural Hematoma(EDH), that too at a site remote to the surgical cavity, is rare. The study presents 3 cases of post operative remote site EDH after tumor resection with review of literature  and an attempt to define and discuss the variables which play a role in determining the occurrence, extent and prognosis of the same.Methods: The study investigated 601 patients who underwent tumor resection in the Department of Neurosurgery, Dr D Y Patil Hospital, from January 2017 to December 2019. All patients had a normal coagulation profile preoperatively. Postoperative remote EDH occurred in 3 patients whose data was examined closely in terms of age, sex, location, final diagnosis and treatment.Results: Of the 601 patients who underwent tumor resection from Jan 2017 to Dec 2019, a total of 3 patients in our study were found to have a post-operative remote site EDH. Two of these patients were male and 1 female. The age range was 35 to 46 years with a mean of 41 years. Neither did any of these patients have a pre-existing hydrocephalus nor were they subjected to a CSF diversion procedure preoperatively. All 3 patients developed EDH on the ipsilateral side wherein 2 of our patients had a hematoma in the ipsilateral frontal region anterior to the surgical cavity while 1 patient developed hematoma in ipsilateral parietal region posterior to surgical cavity. Hematomas were unilateral with no extension to opposite side. Two patients had to be re-operated in an emergency setting while one patient was conservatively managed.  Conclusion: In patients with an expected volume loss via large tumor size, excess blood and CSF loss and a large craniotomy, remote EDH may develop and the  neurosurgeon must have a high index of suspicion for this entity